Antibiotic and metal resistance in a ST395 Pseudomonas aeruginosa environmental isolate: A genomics approach. Issue 1 (15th September 2016) - Teixeira, Pedro; Tacão, Marta; Alves, Artur; Henriques, Isabel
Abstract: We analyzed the resistome of Pseudomonas aeruginosa E67, an epiphytic isolate from a metal-contaminated estuary. The aim was to identify genetic determinants of resistance to antibiotics and metals, assessing possible co-selection mechanisms. Identification was based on phylogenetic analysis and average nucleotide identity value calculation. MLST affiliated E67 to ST395, previously described as a high-risk clone. Genome analysis allowed identifying genes probably involved in resistance to antibiotics (e.g. beta-lactams, aminoglycosides and chloramphenicol) and metals (e.g. mercury and copper), consistent with resistance phenotypes. Several genes associated with efflux systems, as well as genetic determinants contributing to gene motility, were identified. Pseudomonas aeruginosa E67 possesses an arsenal of resistance determinants, probably contributing to adaptation to a polluted ecosystem. Association to mobile structures highlights the role of these platforms in multi-drug resistance. Physical links between metal and antibiotic resistance genes were not identified, suggesting a predominance of cross-resistance associated with multidrug efflux pumps. Highlights: WGS was used to study the resistome of P. aeruginosa E67 from a polluted site. MLST analysis of P. aeruginosa E67 showed that it fits the profile of ST395. A rich arsenal of metal and antibiotic resistance determinants was detected. Genetic determinants contributing to motility were detected. Cross resistance mechanism associated with MDR efflux pumps prevailed.